2014
DOI: 10.1038/ncomms6701
|View full text |Cite
|
Sign up to set email alerts
|

Roquin binding to target mRNAs involves a winged helix-turn-helix motif

Abstract: Roquin proteins mediate mRNA deadenylation by recognizing a conserved class of stem-loop RNA degradation motifs via their Roquin domain. Here we present the crystal structure of a Roquin domain, revealing a mostly helical protein fold bearing a winged helix-turn-helix motif. By combining structural, biochemical and mutation analyses, we gain insight into the mode of RNA binding. We show that the winged helix-turn-helix motif is involved in the binding of constitutive decay elements-containing stem-loop mRNAs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 39 publications
9
35
0
Order By: Relevance
“…One possibility is that Reg1 can recognize a broader range of SL structures than Roquin. However, crystal structures studies revealed that Roquin ROQ domain interacts with the TNF-CDE stem and a triloop with Py-Pu-Py sequences and that Roquin uses mainly non-sequence-specific contacts with the RNA (Schlundt et al, 2014;Schuetz et al, 2014;Tan et al, 2014). Indeed, we found that overexpression of Roquin could affect 3 0 UTRs harboring a stem without the UUC sequence.…”
Section: Discussionmentioning
confidence: 74%
“…One possibility is that Reg1 can recognize a broader range of SL structures than Roquin. However, crystal structures studies revealed that Roquin ROQ domain interacts with the TNF-CDE stem and a triloop with Py-Pu-Py sequences and that Roquin uses mainly non-sequence-specific contacts with the RNA (Schlundt et al, 2014;Schuetz et al, 2014;Tan et al, 2014). Indeed, we found that overexpression of Roquin could affect 3 0 UTRs harboring a stem without the UUC sequence.…”
Section: Discussionmentioning
confidence: 74%
“…Binding of the stem‐loops occurs at the so‐called A‐site, while dsRNA binds at a ‘B‐site’ located between domains I and II, and thus spatially remote from the A‐site (Figures and ). Even though the dsRNA recognition observed by Tan et al is likely to be an artifact of the high RNA concentrations used during crystallization, their findings nevertheless indicate that Roquin‐1 can bind to dsRNA at a second RNA‐binding site. Mutations introduced at each site were used to dissect their individual contributions, and the data suggested that, while the A‐site is critical for mRNA decay, residues in the B‐site may also have an impact on the process …”
Section: Roquin–rna Interactionsmentioning
confidence: 99%
“…The NTA is followed by a helix-turn-helix motif. Interestingly, a helix-turnhelix motif contributes to RNA binding of ROQUIN (67)(68)(69), which implicates a candidate for the RNA-interaction in HCLS1. A coiled-coil region represents the main F-actin binding site and functions synergistically with the helix-turn-helix motif (70 -72).…”
Section: Novel Rna-binding Proteins In Macrophagesmentioning
confidence: 99%